The Impact of Intellectual Capital on the Employee Performance of Smes with the Mediating Role of Organizational Learning - Masoumeh Rastegar; Hani Arbabi (Kurdish Studies, 2023)
Employee performance is one of the basic and important issues that managers and employees of organizations seek to increase. Organizations use different methods and tactics to achieve high performance. Today, due to the complexity of the business environment and the intensity of the competition, organizations realized that the value of intangible assets is a vital determining factor for the competitiveness of the organization. Intellectual capital and organizational learning can be mentioned among the important intangible assets. Therefore, the purpose of this research is to investigate the effect of intellectual capital on the performance of employees with the mediating role of organizational learning. The research method is applied in terms of purpose and descriptive-survey in terms of data collection. The statistical population of the research is made up of SMEs in Tehran. The sample size for this model was determined to be 228 companies. In order to collect data, intellectual capital, organizational learning and employee performance questionnaires were used. To measure the validity of the questionnaire, face validity was used, and for reliability, Cronbach's alpha coefficient and composite reliability were used. In order to test the hypotheses, the structural equation modeling approach with the partial least squares approach was used. The results of research hypotheses showed that intellectual capital and organizational learning have a positive and significant effect on employee performance. Also, the mediating role of organizational learning in the relationship between intellectual capital and employee performance was confirmed.